Metabolic activity of odontoblast-like cells irradiated with blue LED (455 nm) - de Almeida, Leopoldina Fátima Dantas [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Turrioni, Ana Paula Silveira [UNESP]; de-Souza-Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Springer Nature, 2016)
Blue light emitting diodes (LEDs) are frequently used in dentistry for light activation of resin-based materials; however, their photobiostimulatory effects have not yet been fully investigated. This study aimed to investigate the effect of blue LED (455 nm) on the metabolism of odontoblast-like cells MDPC-23. Energy doses of 2 and 4 J/cm2 were used at 20 mW/cm2 fixed power density. MDPC-23 cells were seeded at 10,000 cells/cm2 density in Dulbecco’s modified Eagle’s medium (DMEM) containing 10 % fetal bovine serum (FBS). After 12 h, the culture medium was replaced with new DMEM supplemented with 0.5 % of FBS, and the cells were incubated for further 12 h. After that, single irradiation was performed to the culture, under selected parameters. Cell viability evaluations (Alamar Blue Assay, n = 12), number of viable cells (Trypan Blue Assay, n = 12), morphological analysis by scanning electron microscopy (SEM, n = 2), gene expression (n = 6) of alkaline phosphatase (Alp), collagen (Col-1a1), and dental matrix protein (Dmp-1) (quantitative polymerase chain reaction (qPCR)) were performed 72 h after irradiation. Data were analyzed by Kruskal-Wallis, ANOVA, and Tukey tests (p < 0.05). Direct light application at 4 J/cm2 energy dose had no negative effects on cell viability, while irradiation with 2 J/cm2 reduced cell metabolism. None of doses affected the number of viable cells compared with the control group. The two energy doses downregulated the expression of Alp; however, expression of Col-1a1 and Dmp-1 had no alteration. Cells presented change in the cytoskeleton only when irradiated with 2 J/cm2. In conclusion, the blue LED (455 nm) irradiation, under the evaluated parameters, had no biostimulatory effects on MDPC-23 cells.
Keywords: Cell metabolism; Cell proliferation; Odontoblasts; Phototherapy